Pemberdayaan Ekonomi bagi Disabilitas Melalui Budidaya Jamur di Desa Argodadi - Arni Surwanti; Eni Istiyanti (Universitas Muhammadiyah Yogyakarta, 2022)
People with disabilities have had difficulty finding jobs in the formal sector. However, entrepreneurship gives an alternative for expanding job opportunities. Accordingly, the Covid-19 pandemic in the past two years has caused many businesses to stop. The same applies to businesses run by persons with disabilities in Argodadi Village, Sedayu, Bantul, Yogyakarta. Thus, the Community Partnership Program aims to overcome these problems to obtain additional income from oyster mushroom cultivation. The applied method was through a tutorial and practical. Techniques for implementing activities included training, practice, and mentoring. This activity incited the motivation of persons with disabilities in Argodadi Village. Knowledge and skills also increased in oyster mushroom cultivation, and dry food products from oyster mushrooms could be produced. In addition, the understanding of persons with disabilities in management and entrepreneurship could be improved. The assistance to the Argodadi Village Disability Group was held so that independent entrepreneurs could function properly. The development of oyster mushroom cultivation for persons with disabilities can be done at home.